Viscosity effect on the pressure swirl atomization of an alternative aviation fuel. (15th March 2019) - Dafsari, Reza Alidoost; Lee, Hyung Ju; Han, Jeongsik; Park, Dong-Chang; Lee, Jeekeun
Abstract: Atomization characteristics with viscosity have motivated a number of works to investigate the flow behavior with temperature variation. An experimental study on the atomization characteristics of an aviation fuel was performed to investigate the effects of fuel temperature and its physical properties on the atomization quality and spray structure. A pressure-swirl-type atomizer as a wide-range-applicable nozzle in industrial field and gas turbine combustors was employed to inject the aviation fuel into a gaseous medium. The experiments were conducted by optical diagnostic methods, namely, phase Doppler particle analyzer (PDPA) to measure droplet size and velocity and particle image visualization to capture spray structure. Changes in physical properties of the fuel altered the spray structure, droplet distribution, and atomization quality, which apparently are effective in combustion efficiency and combustion products. Spray development was mapped with the effective parameters from the unstable to fully developed stage. It was also found that decreasing the fuel temperature degrades atomization quality, decreases spray angle and velocity component values, and generates a lower number of fine droplets. Pursuing the effects of injection pressure and temperature on the atomization characteristics led to correlations for predicting spray angle and mean SMD. The findings contribute well to the literature and clarify the atomization process with temperature variation.